Methicillin-resistant S. aureus (MRSA), extended-spectrum (ESBL)- and plasmid-mediated AmpC ß-lactamase -producing Gram-negative bacteria associated with skin and soft tissue infections in hospital and community settings - Selma Uzunović; Branka Bedenić; Ana Budimir; Amir Ibrahimagić; Farah Kamberović; Zlatko Fiolić; Michelle I. A. Rijnders; Ellen E. Stobberingh (Medicinski glasnik, 2015)
Aim: To investigate the characteristics of meticillin-resistant S. aureus (MRSA), extended-spectrum (ESBL), and plasmid-mediated AmpC beta-lactamase producing Gram-negative bacteria causing skin and soft tissue infections (SSTIs) in hospital and outpatient settings of Zenica-Doboj Canton, Bosnia and Herzegovina. Methods: Antibiotic susceptibility was determined by disc-diffusion and broth microdillution methods according to CLSI guidelines. MecA gene was detected by PCR, and genetic characterization of MRSA was performed using spa-typing and the algorithm based upon repeat patterns (BURP). Double-disk-synergy test was used to screen for ESBLs. PCR was used to detect blaESBL alleles. Genetic relatedness of the strains was tested by PFGE. Results: Seventeen in-patients with MRSA, 13 with ESBL-producing Gram-negative bacteria and three patients co-infected with both, were detected. Five MRSA and 16 ESBL-producing Gramnegative bacteria were found in outpatient samples. Klebsiella spp. was isolated in 11 in- and seven outpatients. MLST CC152 was the most prevalent MRSA. Seven (38.9%) Klebsiella spp. yielded amplicons with primers specific for SHV, TEM-1 and CTXM group 1 ?-lactamases. Eight K. pneumonia (44.4%) and 16 (64%) MRSA (including the in- and outpatient) strains were clonally related. Conclusion: The presence of MRSA and ESBL-producing organisms causing SSTIs in the community poses a substantial concern, due to the high morbidity and mortality associated with possible consequent hospital infections.
Keywords: surgical wound infections; CTX-M beta-lactamase; MLST CC152; antibiotic resistance